Different ways to obtain similar results: the development of the corolla and epipetaly in Rubieae (Rubioideae, Rubiaceae) - Alexander Vrijdaghs; Erik Smets; Petra De Block (Plant Ecology and Evolution, 2020)
Background and aims – Rubieae is a tribe in the subfamily Rubioideae characterised by herbaceous plants with verticillate leaves and flowers with a rudimentary or absent calyx and a short, cup-shaped corolla. This is in contrast to the flowers of most other Rubiaceae, in which the tubular corolla is longer than the corolla lobes. Also, the description by Payer, a French 19th century pioneer of floral ontogenetic research, of the floral development in Asperula, Galium, and Rubia deviates from recent insights about the development of tubular corollas, which are based on investigations of flowers of tropical Rubiaceae. Tubular corollas are currently considered as resulting from the development of underlying annular intercalary meristems, whereas Payer explained the tubular corollas in the three taxa by postgenital fusion. We therefore tested both hypotheses in six Rubieae genera, including the three taxa studied by Payer.Methods – Floral ontogeny of ten species in six Rubieae genera based on scanning electron (SEM) and light microscopy (LM). Conclusions – Our results suggest that, in all species studied, the mature phenotype of the corolla as well as the epipetaly of the stamens is caused by a combination of three developmental processes (the development of a stamen-corolla tube, the development of a corolla tube sensu stricto, and postgenital fusion), and the relative moment of activation of each of these processes during floral development (plastochron variation or heterochrony).